2004
DOI: 10.1023/b:jice.0000035925.90831.80
|View full text |Cite
|
Sign up to set email alerts
|

Maximum P-Wave Duration and P-Wave Dispersion Predict Recurrence of Paroxysmal Atrial Fibrillation in Patients with Wolff-Parkinson-White Syndrome after Successful Radiofrequency Catheter Ablation

Abstract: Pd > or = 32.5 ms and Pmax > or = 103.0 ms predict the recurrence of PAF after ablation with acceptable positive and negative predictive values. Pd > or = 32.5 ms is an independent predictor of recurrence of PAF after catheter ablation in patients with WPW syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 30 publications
0
21
0
2
Order By: Relevance
“…There is no consensus about the cutoff value for PD that separates patients who have a history of paroxysmal AF from healthy subjects. Dilaveris et al identified 40 ms as cutoff value of PD to separate patients with paroxysmal AF from controls, while Aytemir et al [45] used a PD cut off value of 32.5 ms in another study, which excluded patients with structural heart disease. The differences in the cutoff values between these studies may be due to the different patients' clinical characteristics and measurement methods used.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus about the cutoff value for PD that separates patients who have a history of paroxysmal AF from healthy subjects. Dilaveris et al identified 40 ms as cutoff value of PD to separate patients with paroxysmal AF from controls, while Aytemir et al [45] used a PD cut off value of 32.5 ms in another study, which excluded patients with structural heart disease. The differences in the cutoff values between these studies may be due to the different patients' clinical characteristics and measurement methods used.…”
Section: Discussionmentioning
confidence: 99%
“…In unique small (n=72 and 78) studies of individuals referred for electrophysiologic study of atrioventricular nodal re-entry tachycardia13 or accessory pathways6 subjects with a history of AF had significantly greater maximum P wave duration and P wave dispersion.…”
Section: P Wave Indices and Afmentioning
confidence: 94%
“…;6 The largest studies (n=500 to 1,353) to examine the relation of P wave duration and dispersion showed correlations ranging from 0.427 to 0.66 8…”
Section: Measurement and Reproducibility Of P Wave Indicesmentioning
confidence: 99%
“…In a study by Hiraki et al, a filtered P‐wave duration of >130 ms on signal‐averaged electrocardiography was an independent predictor of recurrence of AF after AP ablation. In addition, Aytemir et al evaluated the predictive value of the maximum P‐wave duration and P‐wave dispersion on a 12‐lead surface ECG in predicting AF recurrence, and their multivariate analysis showed that only a P‐wave dispersion of ≥32.5 ms was an independent predictor of AF recurrence. In the present study, we evaluated the role of advanced IAB (ie, P‐wave duration of >120 ms accompanied by a biphasic (±) morphology in the inferior leads on 12‐lead surface ECG) in predicting the risk of AF recurrence in patients with WPW syndrome after AP ablation.…”
Section: Discussionmentioning
confidence: 99%